De Baile perfumado a Bacurau: a evolução da produção cinematográfica de Pernambuco como consequência da expansão dos mecanismos de fomento da lei do audiovisual nacional (nº 8.685/1993) - Silva, Samara Taiana de Lima (2022)
Cultural funding in Brazil is historically treated as a subject distant from the priorities of the political agendas. In fact, a costing model was developed based on laws of fiscal benefits concessions for natural and legal persons that were funders of the approved cultural projects. Initiated with the Law Sarney, in 1986, evolving until the implementation of the Law of National Audiovisual, in 1993, which is the legislative object analyzed by the dissertation. From the expansion of its development mechanisms, it was possible to fund the audiovisual chains that, previously, did not find operational conditions to develop. It is from this that the cinematographic industry of Pernambuco starts to expand, reaching the position of the third biggest productive center of the country, finally breaking the historical hegemony of the production developed in the Rio-São Paulo hub. In this perspective, the dissertation has as the general aim to propose a reflection on the significant increase in the number of cinematographic pieces from Pernambuco made feasible by the strengthening process of the Law of National Audiovisual (No. 8,685/1993), with special attention to the period of greater expansion of the performance of the National Film Agency (Ancine), through the development of the Audiovisual Sectorial Fund (FSA). The analyzed period goes from 1996 until 2019, which explains the use of the film names that compose the title. They are, therefore, Baile Perfumado (Perfumed Ball), the first, and Bacurau, the last film from Pernambuco of great exposure funded by the Law of National Audiovisual and its development mechanisms. The research has a descriptive nature, analyzing the investigated reality without proposing a new model of legislation. The methodology is based on a deductive approach, and the chosen procedure is the monographic, using a bibliographical and document review that sustains the raised premises. Adopting a qualitative view, at the same time that evokes quantitative elements, in the form of three analytical charts, the dissertation concludes by reaffirming the raised premise, of expansion of the cinematographic production from Pernambuco caused by the strengthening process of the Law of National Audiovisual and its respective development mechanisms, however, it is far from the interpretation that the referred legislation is about a democratic and easy to access mechanism, resulting, therefore, that the analyzed phenomenon concerns to an isolated case of a good reception of the investigated mechanism.